Morphometry and longitudinal profile of the river cobras sub-basin in planning the location of underground dams - Lima, Alexandre; Lima-Filho, Francisco; Dias, Nildo; Sousa, Anderson; da Silva, Marcia Regina (Revista Ciência Agronômica, 2019)
A study was carried out in the sub-basin of the River Cobras with the aim of evaluating the morphometric characteristics and longitudinal profile of the river basin as a tool for planning the location of underground dams. Morphometric parameters - compactness coefficient, form factor, drainage density and circularity index - were determined. An equilibrium profile was also performed in order to understand the dynamics of erosion and disposition in the sub-basin under study. The results showed that the River Cobras sub-basin is strongly elongated, with low drainage density and high rates of runoff in alluvial areas. The equilibrium profile indicated that the middle course (18 km, stretch 2) of the sub-basin includes a first-order anomaly and is susceptible to erosive processes along this stretch. The lower course (10 km, stretch 3) also has a first order anomaly; however, with a tendency to favour the aggregation of sedimentary material (larger sedimentary bundle) coming from the middle course. The middle course of the sub-basin has potential for the construction of submersible underground dams; whereas in the lower course, the construction of submerged underground dams is recommended. The physical morphometric parameters should not be analysed in isolation, but together with other aspects of surface- and groundwater quality, the recharge area and the social or production demand on the sub-basin.